2008
DOI: 10.1086/592494
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Stellar Magnetic Variation on the Jet Velocity

Abstract: Stellar jets are normally constituted by chains of knots with some periodicity in their spatial distribution, corresponding to a variability of order of several years in the ejection from the protostar/disk system. A widely accepted theory for the presence of knots is related to the generation of internal working surfaces due to variations in the jet ejection velocity. In this paper we study the effect of variations in the inner disk-wind radius on the jet ejection velocity. We show that a small variation in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…These are often interpreted as internal shocks driven by relatively small perturbations in a steady ejection process, and which occur on typical time-scale between ∼ 5 − 20 years. For example in [18] it was shown that the temporal variability of the jet velocity may be associated with a time-varying stellar magnetic field. Episodic jet ejection behaviour may also be associated with variation in the accretion rates or an inflating stellar magnetosphere.…”
Section: Episodic Ejection Of Magnetic Bubbles and Jetsmentioning
confidence: 99%
“…These are often interpreted as internal shocks driven by relatively small perturbations in a steady ejection process, and which occur on typical time-scale between ∼ 5 − 20 years. For example in [18] it was shown that the temporal variability of the jet velocity may be associated with a time-varying stellar magnetic field. Episodic jet ejection behaviour may also be associated with variation in the accretion rates or an inflating stellar magnetosphere.…”
Section: Episodic Ejection Of Magnetic Bubbles and Jetsmentioning
confidence: 99%
“…Hartmann 2009), the origin of knots along stellar jets (e.g. De Colle et al 2008b), the feedback of jets on the core and the star formation efficiency, and the interaction of jets with the ambient medium eventually leading to the generation of turbulence in molecular clouds (e.g. Carroll et al 2009).…”
Section: Introductionmentioning
confidence: 99%